Avaliação dos impactos acadêmicos do REUNI nos cursos de graduação do Instituto de Cultura e Arte da UFC na experiência dos gestores - Souza, João Paulo Bastos Moreira de (2020)
On April 24, 2007, the Federal Government created the Education Development Plan and with it the Support Program for Federal University Restructuring and Expansion Plans (Reuni). Considering that Reuni had broad implications for higher education in Brazil, this study aims to assess the academic impacts of the quality of education arising from the adhesion and implementation of Reuni at the Federal University of Ceará, based on the perception and experience of managers. Graduation courses in Social Communication (qualifications in Journalism and Advertising and Propaganda), Stylism and Fashion, Music Education and Philosophy, which formed the UFC Institute of Culture and Art, were specifically chosen. Reuni brought goals that were agreed between MEC and universities. Depending on the objectives of the work, this study proposes to evaluate this public educational policy through a historical overview, the contextualization of public policies aimed at education and the circumstances of implementation of Reuni. For that, the evaluation perspective used in the study refers to the post-constructivist conception of Lejano (2012), which uses an experiential evaluation aiming to reach a high level of the answers to our questions. A case study of the undergraduate courses mentioned above was prepared. The methodological path included a qualitative research, with the help of quantitative data. Research procedures for documentary and bibliographic surveys and field research were carried out with the collection of data from semi-structured interviews with ICA managers, drawing their institutional trajectory and verifying what impacts actually occurred, through a Content Analysis methodology of Bardin (2011). With the joining and implementation of Reuni, the courses object of this study went through a readjustment in their physical and administrative structures. Goals were met, such as increasing the number of admission slots, reducing dropout rates and filling vacant vacancies. There was an academic-curricular restructuring in each course and policies for inclusion, student assistance and student mobility were implemented. We conclude that the institutional evaluation together with the fulfillment of these goals, contributed significantly to the increase in the quality of teaching in the referred courses